Family farm business and access to rural development polices: A demographic perspective - Luca Bartoli; Marcello De Rosa (Agricultural and Food Economics, 2013)
This article aims to show the ability of family farms in obtaining funds from rural development policies. Under the hypothesis that family farms' characteristics influence their access to policies, the perspective of analysis is demographic. In the paper two demographic viewpoints are investigated, to emphasize the role of the family composition in fostering strategic farms' decisions: the localization in the life cycle and the presence of assistants. The empirical test is provided for an Italian region: the funds of rural policies gained by family farms are examined, divided up into the three main strategic axes of the rural development plan. The results of the analysis highlight some interesting differences between the two demographic perspectives; the presence of assistants influences a farm's strategic process and increases the access to rural policies. This induces normative consequences in terms of the possible articulation of policies aimed at sustaining family farms.
Keywords: 330; Rural development policies; Family farm business